2016
DOI: 10.15740/has/ijas/12.2/163-166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient management on growth, yield and quality of Kharif groundnut

Abstract: : Agronomic investigation was carried out to study the influence of nutrient management on growth yield and quality of Kharif groundnut. The results revealed that, the balanced nutrition through STCR equation proved its superiority by recording significantly maximum growth and yield attributes during both years. Application of fertilizer as per STCR (25 q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This might be due to higher yield of onion than potato in soybean based cropping sequence. Similar results were reported by Pacharne (2014) and Thorat et al (2018).…”
Section: Crop Sequencessupporting
confidence: 92%
“…This might be due to higher yield of onion than potato in soybean based cropping sequence. Similar results were reported by Pacharne (2014) and Thorat et al (2018).…”
Section: Crop Sequencessupporting
confidence: 92%
“…This might be because of balanced nutrition application in yield target approach which increases the uptake of essential nutrients and accelerates the activities of cell elongation and cell multiplication as well as metabolic activities resulted in increasing all the growth attributes of fruit. Similar results were recorded by Pacharne et al (2016) [7] and Shreenivasa et al (2017) [8] 3.3 Cost of cultivation (Rs/acre) Two years data on cost of cultivation is (presented in Table 2 and fig. 1) divided into two categories: fixed and variable costs.…”
Section: Fruit Yield Kg/polesupporting
confidence: 85%
“…Saha and Prasad et al (2010) reported that "application of 50 per cent NPK + 50 per cent nitrogen through FYM increased the uptake of N, P and K by maize crop (115, 24 and 126 kg ha-1, respectively) as compared to different doses of inorganic fertilizers in sandy clay loam soils. Sheetal et al [6] observed that the highest nutrient content and uptake was recorded in 150% RDF (37.5:75:37.5 kg ha-1) and found at par with 5t FYM ha-1 + 50% RDF + neem cake 500 kg ha-1 + biofertilizers in pod and haulm in groundnut respectively".…”
Section: Phosphorus Content and Uptakementioning
confidence: 99%